ANALISIS BREAK EVEN POINT USAHATANI CABAI RAWIT (Capsicum frutensces L) DI DESA BELANGIAN KECAMATAN ARANIO KABUPATEN BANJAR - Aulia Rahmah; Zulipah Mahdalena; Fenny Refiana (Fakultas Pertanian UVAYA Banjarmasin, 2021)
This study aimed to determine the coct, revinue and break even point of Cayenne pepper in Belangian villige, Aranio District. The method used in the reasearch is survey and observation method. The determination of the number of farmers using Porposive Sampling Method in order to obtain 98 sample farmers. The results of this study obtained an average production of 6955 kg/farmer. The average variable cost incurred by farmers in Cayenne pepper farming is Rp. 5.423.902/farmers. While the average fixed costs incurred by farmers is Rp. 72.269/farmer. So that the average total cost is Rp. 5.496.171/farmer. Break Even Point (BEP) revenue obtained is Rp. 1.129.203/farmer, Break Even Point (BEP) of the production volume obtained is Rp. 219.847/kg. And Break Even Point (BEP) of price is Rp. 24.999/farmer. From the value of BEP, is can be stated that the Cayenne pepper farming in Belangian villege has passed the BEP value, so that the farming has benefited and can be continued